2020
DOI: 10.3390/ijms21062175
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of SDF-1 Functionalized 3D-Printed Cell-Free Scaffolds for Bone Tissue Regeneration

Abstract: Large segmental bone defects occurring after trauma, bone tumors, infections or revision surgeries are a challenge for surgeons. The aim of our study was to develop a new biomaterial utilizing simple and cheap 3D-printing techniques. A porous polylactide (PLA) cylinder was printed and functionalized with stromal-derived factor 1 (SDF-1) or bone morphogenetic protein 7 (BMP-7) immobilized in collagen type I. Biomechanical testing proved biomechanical stability and the scaffolds were implanted into a 6 mm critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 61 publications
(68 reference statements)
2
21
0
Order By: Relevance
“…To analyze degradation, longer-lasting animal studies are necessary. The transplantation of a similarly dimensioned, 3D-printed, porous tube structure into a plate-stabilized 5 mm defect in the rat femur by two authors of this study showed signs of degradation of the implanted PLA scaffold after eight weeks of healing time [47]. It is concluded that, for a sufficient analysis of the degradation, a standing time of at least six months is necessary.…”
Section: Scaffold Design Mechanics and Biological Aspectsmentioning
confidence: 62%
See 1 more Smart Citation
“…To analyze degradation, longer-lasting animal studies are necessary. The transplantation of a similarly dimensioned, 3D-printed, porous tube structure into a plate-stabilized 5 mm defect in the rat femur by two authors of this study showed signs of degradation of the implanted PLA scaffold after eight weeks of healing time [47]. It is concluded that, for a sufficient analysis of the degradation, a standing time of at least six months is necessary.…”
Section: Scaffold Design Mechanics and Biological Aspectsmentioning
confidence: 62%
“…The individual hollow column subunit thus offers all biologically relevant features and could be tested individually in the established small animal model, in the future [43][44][45][46]. Transplantation of a similarly dimensioned, 3D-printed, porous hollow column structure into a plate-stabilized 5 mm defect in the rat femur by two authors of this study showed promising healing results [47]. Transfer to a large animal model is conceivable, since current data indicate that scaffolds based on 3D printed fused filament fabrication can be effective for the treatment of large bone defects in large animals [9,[48][49][50].…”
Section: Process Developmentmentioning
confidence: 89%
“…We and others combined PLA and collagen to take advantage of the different properties of these materials: The mechanical stability of polylactide, although lower than bone, is still high enough to be used as bone substitute[ 26 ], and the soft material collagen, which can be modified with various bioactive molecules[ 18 ]. We and others printed PLA together with collagen to induce tissue regeneration in different bone defects[ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lauer et al developed a 3D-printed polylactide (PLA) cylinder and functionalized it with SDF-1 for use in a rat femur bone defect. They found that the addition of SDF-1 resulted in osteoinductive effects [ 47 ]. In our study, the Gel/HA–HAP–SDF-1 composite we made showed similar results.…”
Section: Discussionmentioning
confidence: 99%